METODE PEMBELAJARAN PAI PADA ANAK USIA DINI - Rida Nurfarida; Ima Frima Fatimah; H. Uus Ruswandi; Bambang Samsul Arifin (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
The problem of PAI learning methods in PAUD is very important. Because early childhood is in the stage of getting bored quickly, the learning method is not interesting, and the monotony will have an impact that the PAI learning objectives are not achieved The method must be interesting, attractive, and fun, children are actively involved, not dominated by the teacher. This research method uses qualitative where the data is presented in a narrative manner rather than based on statistics. The research method uses a qualitative approach, collecting data through interviews, observation and documentation studies. The purpose of this study was to determine the PAI learning method used in PAUD. The results showed that the PAI learning methods that are often used in PAUD are: habituation, lectures, playing, singing, demonstrations, storytelling questions and answers direct practice and assignment.